Preparation and application of solvent-free fluorine functionalized electrocatalyst
A solvent-free fluorine-functionalized electrocatalyst with a 1D/3D bridge structure addresses the OER barrier and PET electro-oxidation, enhancing hydrogen production and PET recycling efficiency, producing high-value formic acid and managing marine microplastics.
Patent Information
- Application Number
- CN202411315848.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The high thermodynamic barrier of the anodic oxygen evolution reaction (OER) and low added value of products in electrocatalytic water decomposition, along with the challenges of PET recycling and microplastic management, necessitate the development of efficient and low-cost catalysts that can drive hydrogen evolution and PET electro-oxidation.
A solvent-free fluorine-functionalized electrocatalyst is prepared by etching fluorine onto carbon nanocages and cobalt-nickel alloy nanotubes, forming a 1D/3D bridge structure with a rich mesoporous structure and high conductivity, enabling trifunctional catalysis for hydrogen evolution, oxygen evolution, and PET electro-oxidation, and incorporating a material that can be used for hydrogen production, and the electro-oxidation of PET microplastics.
The electrocatalyst reduces the energy barrier for water electrolysis and produces high-value formic acid while managing marine microplastics, achieving high current densities and efficient electron transfer.
Smart Images

Figure CN119177468A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of novel material preparation, and in particular relates to the preparation and application of solvent-free fluorine-functionalized electrocatalysts. Background Art
[0002] The combustion of fossil fuels produces a huge amount of greenhouse gas carbon dioxide, causing global climate change and global warming. Hydrogen energy has become an ideal green energy source to replace fossil fuels due to its high volatility and energy density. So far, electrocatalytic water decomposition to produce hydrogen is considered to be the most promising way to produce hydrogen due to its advantages such as pollution-free and renewable. However, there are still many problems in the process of electrocatalytic water decomposition to produce hydrogen, which restricts their practical application, such as the high thermodynamic barrier of the anodic oxygen evolution reaction (OER) and the low added value of the product. Therefore, the rational design and preparation of efficient and low-cost catalysts and the replacement of OER by electro-oxidation of organic molecules are urgent issues to be solved in the field of low-cost electrocatalytic hydrogen evolution.
[0003] Polyethylene terephthalate (PET) is a non-toxic polyester plastic widely used in food packaging and beverage bottles. PET recycling strategies usually have problems with carbon emissions and low selectivity, which bring about ecological risks and resource waste that cannot be ignored. Therefore, upcycling PET plastics in a sustainable way is a necessary and meaningful task to develop the value of waste PET plastic resources. Fortunately, the polyester chain of PET can be easily hydrolyzed in alkaline media, and the products mainly contain terephthalic acid (TPA) and ethylene glycol (EG), while the oxidation potential of EG is lower than that of OER and can be coupled with HER reaction. EG is oxidized and the final product is converted into formate, which can replace antibiotic additives as a safe growth promoter in livestock food. This saves energy while producing high value-added chemicals at the anode. Therefore, developing a catalyst that can effectively drive the HER process while meeting the high activity requirements of PET upgrading is of practical significance to energy engineering and environmental engineering.
[0004] Heteroatom doping is crucial for optimizing the adsorption of reaction intermediates on the surface of carbon substrates or transition metal active sites. Among various heteroatoms, F doping has attracted extensive research in recent years. Due to its large electronegativity, it leads to in-plane topological defects in the carbon skeleton, recalibrates the hybridized electron orbitals and bond lengths, induces charge delocalization, and thus obtains high conductivity. In addition, the metal-F bond is easily broken in alkaline media, and F ions are rapidly exchanged to form a phase that is conducive to the adsorption of intermediates. However, the choice of F sources is limited. Currently, most reported F sources are ammonium fluoride, which limits its application due to its instability and high temperature processing process. Etching ordered F directly on carbon nanocage substrates through a fast, solution-free plasma process is an effective means to solve the above problems. Summary of the invention
[0005] The purpose of the present invention is to reduce the energy barrier of water electrolysis reaction and improve the added value of products, and to provide a solvent-free fluorine-functionalized electrocatalyst and its use in microplastic electro-oxidation coupled hydrogen evolution reaction.
[0006] A solvent-free fluorine-functionalized electrocatalyst is prepared by the following method:
[0007] A. Preparation of carbon nanocages (CNCs):
[0008] 1) Add 50-200 mg SiO 2 Mix with 50-200 mg P123 and add to a Tris-HCl solution with a pH of 8.0-9.0, stir at room temperature, add 150-300 mg dopamine, and stir again;
[0009] 2) The obtained precipitate was washed with deionized water and dried in a vacuum oven. The dried powder was heated in a tube furnace under N 2 At 5 ℃ min −1 The temperature was raised to 700-900 °C at a heating rate and kept constant for 2 h to obtain black hollow porous carbon nanocages, denoted as CNCs.
[0010] B. Preparation of carbon nanotubes / cobalt-nickel alloys / carbon nanocages CNTs / CoNi / CNCs:
[0011] 1) Weigh 0.9-1.1g Co(NO 3 ) 2 6H 2 O and 0.5 g Ni(NO 3 ) 2 6H 2 O is placed in a beaker, 180-220 mg of CNCs are added, and kept in a molten state in an oven;
[0012] 2) Take out and wash with deionized water, and vacuum dry, which is recorded as CoNi / CNCs;
[0013] 3) Place the CoNi / CNS prepared in step (2) in a tube furnace, and weigh a certain amount of dicyandiamide and place it upstream of the tube furnace. 2 At 5 ℃ min −1 The heating rate was raised to 700 °C, and the mass ratio of dicyandiamide to CoNi / CNCs was 10-30:1;
[0014] 4) Cooling to obtain carbon nanotubes / cobalt-nickel alloy / carbon nanocages, labeled as CNTs / CoNi / CNCs;
[0015] C. Preparation of solvent-free fluorinated carbon nanotubes / cobalt-nickel alloy / carbon nanocages:
[0016] Place CNTs / CoNi / CNCs in a plasma chamber, CF 4 As a F source, F was doped on the surface of CNTs / CoNi / CNCs by plasma etching to obtain an electrocatalyst, which was denoted as F / CNTs / CoNi / CNCs.
[0017] Step A, 1) the SiO 2 and P123 in a 1:1 ratio, with 50 ml of Tris-HCl solution, pH 8.5; stir at room temperature for 30 min, then add dopamine, and stir at room temperature for another 24 h;
[0018] Step B, 1) Co(NO 3 ) 2 6H 2 O was 1.0 g, CNCs was added in an amount of 200 mg, and the mixture was kept in a molten state in an oven at 120 °C.
[0019] The etching power in step C is 100 W and the etching time is 10 min.
[0020] The solvent-free fluorine-functionalized electrocatalyst is used in the preparation of hydrogen evolution, oxygen evolution and polyethylene terephthalate electro-oxidation catalyst electrode materials.
[0021] The electrode material is prepared by the following method:
[0022] 1) Weigh F / CNTs / CoNi / CNCs and disperse them in ethanol solution, add Nafion solution, and perform ultrasonic dispersion to obtain catalyst ink;
[0023] 2) The nickel foam was ultrasonicated in 0.9-1.1 M HCl, acetone and ethanol respectively and dried in vacuum;
[0024] 3) The catalyst ink prepared in step 1) is evenly coated on the surface of the nickel foam and dried under a baking lamp to obtain a working electrode.
[0025] 5 mg of F / CNTs / CoNi / CNCs in step 1) was dispersed in 1000 μL of 50% ethanol solution, and 50 μL of Nafion solution was added, and ultrasonic dispersion was performed for 30 min; HCl in step 2) was 1 M HCl.
[0026] A PET electro-oxidation coupled hydrogen evolution system, using the working electrodes as cathode and anode respectively, using Nafion membrane to separate the cathode and anode of the H-type electrolytic cell cup, the anode electrolyte is a 1 M KOH PET microplastic suspension solution, and the cathode electrolyte is 1 M KOH.
[0027] The PET microplastic suspension solution is prepared by the following method: PET bottles are cut into pieces and placed in a 6 M KOH solution, and stirred at 80° C. to obtain a PET microplastic suspension solution.
[0028] The present invention provides a solvent-free fluorine-functionalized electrocatalyst which can be used for hydrogen evolution reaction (HER), OER and PET microplastic electrooxidation. Firstly, a triblock copolymer P123 and spherical SiO 2 Micelle is formed between the templates, and after dopamine self-polymerization and template removal, mesoporous carbon nanocage is formed. The large specific surface area and rich mesoporous structure can not only expose more active sites, but also promote the mass transfer efficiency of electrons and enhance the electrocatalytic performance. At the same time, the nitrogen atoms of the dopamine precursor provide sites for metal modification, and the cobalt-nickel alloy is anchored to the surface of the carbon nanocage through the metal-N bond. Secondly, cobalt-nickel alloy is used as the catalytic site and dicyandiamide is used as the carbon source to grow carbon nanotubes to form a 1D / 3D bridge structure. The interconnected three-dimensional nanotube array provides abundant channels, enhances conductivity, promotes the rapid transfer of electrons or ions, and accelerates the reaction rate. Finally, through solvent-free CF 4 After plasma treatment, F atoms are grafted on the catalyst surface, and the metal-F bond is easily broken in an alkaline environment, forming a real active species in the electrocatalytic reaction process. The electrocatalyst provided by the present invention can achieve trifunctional catalysis, and at the same time, through the strategy of replacing OER with electro-oxidation of PET microplastics, while saving energy in hydrogen production, the generation of high value-added products is achieved at the anode, providing broad application prospects for the exploitation of "marine hydrogen mines" and the management of marine microplastics. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 SEM image of the carbon nanocage prepared by the present invention;
[0030] Figure 2 Transmission electron microscope image of fluorine-functionalized carbon nanotube / cobalt-nickel alloy / carbon nanocage prepared by the present invention;
[0031] Figure 3 LSV diagram of hydrogen evolution reaction of the catalysts prepared in Examples 1, 2 and 3 of the present invention;
[0032] Figure 4 LSV diagram of oxygen evolution reaction of the catalysts prepared in Examples 1, 2 and 3 of the present invention;
[0033] Figure 5 Comparison diagram of PET electro-oxidation and oxygen evolution reaction in Example 5 of the present invention. DETAILED DESCRIPTION
[0034] Example 1 Preparation of Carbon Nanocages
[0035] 1) 50 mg SiO 2 and P123 in a 1:1 ratio, and added to 50 ml Tris-HCl solution at pH 8.5, stirred at room temperature for 30 min, then added 150 mg dopamine, and stirred at room temperature for 24 h;
[0036] 2) The obtained precipitate was washed with deionized water for three times and dried in a vacuum oven. The dried powder was heated in a tube furnace at N 2 At 5 ℃ min −1 The temperature was raised to 900 °C at a heating rate and kept constant for 2 h. The obtained black hollow porous carbon nanocages were denoted as CNCs.
[0037] Figure 1 The SEM image of the prepared carbon nanocage. In a typical synthesis process, P123 is prepared by SiO 2 Hydrogen bonding interactions between alcohol groups and ether oxygen of PEO blocks adsorbed on SiO 2 surface, forming a single bundle. 2 The electrostatic attraction between the SiO 2 The surface was polymerized to form a polydopamine shell. 2 A single-layer mesoporous ultrathin N-doped carbon structure was generated on the surface. Finally, the central SiO 2 Nanospheres were synthesized to obtain a hollow 3D mesoporous carbon nanocage structure. It can be seen that the synthesized hollow carbon nanocage maintained a uniform spherical structure with a diameter of about 330 nm.
[0038] Example 2 Preparation of carbon nanotubes / cobalt-nickel alloy / carbon nanocages
[0039] 1) Weigh 1.0 g Co(NO 3 ) 2 6H 2 O and 0.5 g Ni(NO 3 ) 2 6H 2 O was placed in a beaker, 200 mg of the CNCs in Example 1 were added, and the mixture was kept in a molten state in an oven at 120 °C. After 15 min, the mixture was taken out and washed with deionized water, and dried in a vacuum, which was recorded as CoNi / CNCs;
[0040] 2) Place the CoNi / CNS prepared in step (1) in a tube furnace, and weigh a certain amount of dicyandiamide and place it upstream of the tube furnace. 2 At 5 ℃ min −1 The heating rate was raised to 700 °C, and the mass ratio of dicyandiamide to CoNi / CNCs was 20:1;
[0041] 3) Cooling to obtain carbon nanotubes / cobalt-nickel alloy / carbon nanocages, which are labeled as CNTs / CoNi / CNCs.
[0042] Example 3 Preparation of solvent-free fluorinated carbon nanotubes / cobalt-nickel alloy / carbon nanocages
[0043] The CNTs / CoNi / CNCs in Example 2 were placed in a plasma chamber. 4 As the F source, F was doped on the surface of CNTs / CoNi / CNCs by plasma etching with a power of 100 W and an etching time of 10 min. The obtained sample was recorded as F / CNTs / CoNi / CNCs.
[0044] Figure 2 The transmission electron micrograph of fluorine-functionalized carbon nanotubes / cobalt-nickel alloy / carbon nanocages is shown. The criss-crossed carbon nanotubes exist between the carbon nanocages. The interconnected three-dimensional nanotube arrays provide abundant channels, enhance conductivity, promote the rapid transfer of electrons or ions, and accelerate the reaction rate.
[0045] Example 4 Depolymerization of PET microplastics
[0046] Weigh 10.0 g of a mineral water bottle, cut it into pieces and place it in a 6 M KOH solution. Stir it at 80 °C for 12 h to obtain a PET microplastic suspension.
[0047] Example 5 Preparation and performance testing of electrode materials used as catalysts for hydrogen evolution, oxygen evolution and polyethylene terephthalate (PET) electrooxidation
[0048] 1) The F / CNTs / CoNi / CNCs described in Example 3 was used as a catalyst to prepare a catalyst ink. 5 mg of F / CNTs / CoNi / CNCs was weighed and dispersed in 500 μL of anhydrous ethanol and 500 μL of deionized water, and 50 μL of Nafion solution was added, and ultrasonic dispersion was performed for 30 min.
[0049] 2) Cut the nickel foam into 1*2 cm size, ultrasonicate in 1 M HCl, acetone and ethanol for 15 min, and vacuum dry. Pipette 50 μL of the catalyst ink prepared in 1) and evenly coat it on the nickel foam surface. The coating area is controlled to 1 cm 2 , and dried under a baking lamp as a working electrode.
[0050] 3) Electrocatalytic performance test: Using Hg / HgO as the reference electrode and graphite electrode as the counter electrode, the electrochemical performance of hydrogen evolution, oxygen evolution and PET electrooxidation was tested in the Chenhua CHI760 electrochemical workstation. 1 M KOH was selected as the electrolyte for the electrochemical test of hydrogen evolution and oxygen evolution, and 1 M KOH PET microplastic solution was selected for PET electrooxidation.
[0051] Figure 3 The hydrogen evolution performance of the catalysts prepared in Examples 1, 2, and 3 is shown. It can be seen that F / CNTs / CoNi / CNCs / NF exhibits excellent HER catalytic activity, achieving 10 mA cm at an overpotential of 187 mV. -2 The current density is higher, especially when the current density is as high as 300 mA cm -2 When , the overpotentials of F / CNTs / CoNi / CNCs / NF (402 mV) and Pt / C (383 mV) are almost the same.
[0052] Figure 4 The oxygen evolution performance of the catalysts prepared in Examples 1, 2, and 3 is shown. It can be seen that F / CNTs / CoNi / CNCs / NF also exhibits excellent OER performance, reaching 10 mA cm at an overpotential of 315 mV. -2 The current density can reach 300 mA cm -2 Industrial grade current density.
[0053] Example 6 Construction of PET electro-oxidation coupled hydrogen evolution device
[0054] The working electrodes prepared in Example 5 were used as cathode and anode, respectively, and the cathode and anode of the H-type electrolytic cell cup were separated by a Nafion membrane. The anode electrolyte was a 1 M KOH PET microplastic solution, and the cathode electrolyte was 1 M KOH. The device produced high-value-added formic acid at the anode while producing hydrogen at the cathode, and reduced the reaction overpotential.
[0055] Figure 5 The LSV curve of electrolytic PET shows that a potential of only 1.4 V is required to reach 100 mA cm -2The current density is 250 mV lower than that of OER, which greatly reduces the potential for driving water decomposition while obtaining high-value formic acid.
Claims
1. A solvent-free fluorinated electrocatalyst prepared by the following method: A. Preparation of carbon nanocages (CNCs): 1) Mix 50-200 mg SiO2 and 50-200 mg P123, add to Tris-HCl solution with pH 8.0-9.0, stir at room temperature, add 150-300 mg dopamine, and stir again; 2) The obtained precipitate was washed with deionized water and dried in a vacuum oven. The dried powder was heated in a tube furnace at 5 °C min under N2 atmosphere. −1 The temperature was raised to 700-900 °C at a heating rate and kept constant for 2 h to obtain black hollow porous carbon nanocages, denoted as CNCs. B. Preparation of carbon nanotubes / cobalt-nickel alloy / carbon nanocages CNTs / CoNi / CNCs: 1) Weigh 0.9-1.1g Co(NO3)2 6H2O and 0.5g Ni(NO3)2 6H2O into a beaker, add 180-220mg CNCs, and keep them in a molten state in an oven; 2) Take out and wash with deionized water, and vacuum dry, which is recorded as CoNi / CNCs; 3) Place the CoNi / CNS prepared in step (2) in a tube furnace, weigh a certain amount of dicyandiamide and place it upstream of the tube furnace. −1 The heating rate was raised to 700 °C, and the mass ratio of dicyandiamide to CoNi / CNCs was 10-30:1; 4) Cooling to obtain carbon nanotubes / cobalt-nickel alloy / carbon nanocages, labeled as CNTs / CoNi / CNCs; C. Preparation of solvent-free fluorinated carbon nanotubes / cobalt-nickel alloy / carbon nanocages: CNTs / CoNi / CNCs were placed in a plasma chamber, CF4 was used as a F source, and F was doped on the surface of CNTs / CoNi / CNCs by plasma etching to obtain an electrocatalyst, which was recorded as F / CNTs / CoNi / CNCs.
2. A solvent-free fluorine-functionalized electrocatalyst according to claim 1, characterized in that: Step A, 1) the SiO2 and P123 are mixed in a ratio of 1:1, the solution of Tris-HCl solution is 50 ml, pH 8.5; dopamine is added after stirring at room temperature for 30 minutes, and then stirred at room temperature for another 24 hours.
3. A solvent-free fluorine-functionalized electrocatalyst according to claim 2, characterized in that: Step B: 1.0 g of Co(NO3)2 6H2O described in step 1) and 200 mg of CNCs are added, and the mixture is kept in a molten state in an oven at 120°C.
4. A solvent-free fluorine-functionalized electrocatalyst according to claim 3, characterized in that: The etching power in step C is 100 W and the etching time is 10 min.
5. Use of a solvent-free fluorine-functionalized electrocatalyst according to claim 1 in the preparation of hydrogen evolution, oxygen evolution and polyethylene terephthalate electro-oxidation catalyst electrode materials.
6. The use according to claim 5, characterized in that: The electrode material is prepared by the following method: 1) Weigh F / CNTs / CoNi / CNCs and disperse them in ethanol solution, add Nafion solution, and perform ultrasonic dispersion to obtain catalyst ink; 2) The nickel foam was ultrasonicated in 0.9-1.1 M HCl, acetone and ethanol respectively and dried in vacuum; 3) The catalyst ink prepared in step 1) is evenly coated on the surface of the nickel foam and dried under a baking lamp to obtain a working electrode.
7. The use according to claim 6, characterized in that: 5 mg of F / CNTs / CoNi / CNCs in step 1) was dispersed in 1000 μL of 50% ethanol solution, and 50 μL of Nafion solution was added, and ultrasonic dispersion was performed for 30 min; HCl in step 2) was 1 M HCl.
8. A PET electro-oxidation coupled hydrogen evolution system, characterized in that: The working electrodes described in claim 6 are used as cathode and anode respectively, and the cathode and anode of the H-type electrolytic cell cup are separated by a Nafion membrane. The anode electrolyte is a PET microplastic suspension solution of 1 M KOH, and the cathode electrolyte is 1 M KOH.
9. A PET electro-oxidation coupled hydrogen evolution system according to claim 8, characterized in that: Depolymerization of PET microplastics: PET bottles were cut into pieces and placed in a 6 M KOH solution, stirred at 80 °C for 12 h to obtain a PET microplastic suspension.
